(untitled) (Plant Tissue Culture and Biotechnology, 2010)
Multiple shoots from nodal explants of Pogostemon cablin Benth. MS supple-mented with 0.5 mg/l BAP initiated a mean of 45.66 shoots/nodal explant. Within four weeks of initiation, regenerated multiple shoots attained a height of 3.6 cm. Subsequent transfer of these in vitro derived nodal segments onto MS supplemented with BAP and Kn ( 0.5 mg/l), induced a mean of 62.45 shoots. Higher concentration of either BAP or Kn more than 0.5 mg/l resulted in callus proliferation and showed hyperhydric shoots with morphological abnormalities. Rooting was readily achieved upon transfer of shoots on half strength MS supplemented with 100 mg/l activated charcoal. Rooted shoots, following acclimatization in greenhouse, were successfully transferred to soil with 91% survival. Also shoots regenerated in vitro were directly transplanted to soil and acclimatized. Tissue cultured plants were analyzed for oil content by employing gas chromatography and found that the patterns were similar to mother plants. This confirms the true to type nature of micropropagated plants. Key words: Micropropagation, Direct regeneration, Pogostemon cablin, organogenesis D.O.I. 10.3329/ptcb.v20i1.5971 Plant Tissue Cult. & Biotech. 20(1): 81-89, 2010 (June)